Otomatisasi Monitoring Stok Logistik Terdistribusi Berbasis Rapid Application Development, GAS, dan Telegram Bot - Wahyu Setianto Dwi Aji; Asri Samsiar Ilmananda (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2026)
Daily logistics reporting latency on an H+1 scale across 24 active warehouses at PT Telkom Akses Area Malang triggers the risk of delayed Network Terminal Equipment (NTE) device installations at customers' homes due to stock shortage (understock) constraints, as well as storage space inefficiency caused by asset accumulation (overstock). This condition stems from conventional workflows where warehouse admins must manually recapitulate data using passive spreadsheets. This study aims to transform this manual mechanism into a real-time automated monitoring system using the Rapid Application Development (RAD) method. The developed system integrates Google Apps Script (GAS) technology as a cloud-based computational logic hub and the Telegram Bot API as an automated notification gateway to the managerial coordination group. Inventory control is autonomously managed by a two-way control logic based on Safety Stock (SS) and Maximum Stock (Smax) parameters to monitor 8,256 units of active ONT devices. Implementation results demonstrate that this automation successfully reduces the latency of sending critical stock reports from a daily scale to under 5 seconds with a 0% error rate (zero-error rate). The main contribution of this research is providing proactive stock visibility for warehouse admins, eliminating the risk of human error due to manual input processes, and accelerating strategic decision-making in the Supply Chain division of PT Telkom Akses Area Malang to maintain service sustainability for customers.